Teaching Students to Understand and Understand Learning Texts (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article focuses on the use of PIRLS International Assessment Program requirements in teaching primary school students to understand and understand instructional texts, showing the content of PIRLS international study and ways to teach PIRLS to work on text based on the requirements of the International Assessment Study.